Levonorgestrel intrauterine system for heavy menstrual bleeding: a real-world experience from a tertiary centre in Northern India - Thakur, Meenakshi; Gupta, Amit; Verma, Meenakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Heavy menstrual bleeding (HMB) affects quality of life and health in reproductive-age women. Levonorgestrel intrauterine system (LNG-IUS) offers a conservative treatment option. This study aimed to evaluate the clinical efficacy and acceptability of LNG-IUS in women with HMB. Methods: Retrospective analysis of 63 women (32-50 years) with HMB at Dr. RPGMC, Kangra, over two years. Follow-up was conducted at 1, 3, 6, and 12 months. Data included demographics, clinical presentation, hematological investigations, ultrasonographic findings, follow-up outcomes, and patient satisfaction scores. Results: Mean age was 44.28 years; 50.79% were 45-50 years. Majority (68.25%) were para 2; 96.82% were married. Socioeconomic status varied, with 25.39% in the upper-lower class. The most common diagnosis was dysfunctional uterine bleeding (57.14%), followed by fibroid uterus (25.39%), adenomyosis (11.11%), and endometriosis (6.34%). Comorbidities included hypertension (15.87%) and diabetes (11.11%). Hemoglobin analysis showed moderate anemia in 52.38% and severe anemia in 26.98%. Bleeding patterns improved significantly: at 1 month, 57.14% had scanty flow; by 3 months, 74.60% reported reduced bleeding; at 6 months, 86.27% had scanty or no bleeding. By 12 months, 41.17% developed amenorrhea. Expulsion occurred in 2 cases; 2 others requested removal. Overall, 82.35% were satisfied with bleeding pattern; 98.03% had no dysmenorrhea. Social, sexual life, and mobility improved notably. Satisfaction assessment showed 80.38% of patients were either satisfied or very satisfied. Conclusions: LNG-IUS is effective, safe, and well accepted for treating HMB, particularly in resource-limited settings. Its impact on reducing blood loss, correcting anemia, and improving life quality supports its wider use.